DEVELOPMENT OF E-MARKETPLACE FOR MARKETING AGRICULTURAL PRODUCTS (CASE STUDY IN TUMARATAS VILLAGE) - Prisilia Lumentah, Sweety; Benny Pinontoan; Edwin Tenda; Eliasta Ketaren (STMIK TIME, 2024)
Tumaratas is an agricultural village where most of the people's livelihood is farming. However, sales of agricultural products are still carried out traditionally and are tied to certain times, this can make it difficult for farmers and consumers to carry out the buying and selling process whenever they want. Limited market reach, farmers still rely on intermediaries or retailers so that products are only available in local shops or traditional markets, and do not reach consumers outside the area. E-Marketplace is an intermediary media that brings together sellers and buyers on the internet, helping sellers market and offer merchandise on the internet. The aim of this research is to build and develop an E-Marketplace for farmers as a forum for promoting and marketing their agricultural products and to make it easier for consumers to find the agricultural products they want. This e-Marketplace was developed using the PHP programming language with the Laravel framework and MySQL as the database. With the development of this E-Marketplace, it is hoped that it can help local farmers market their agricultural products and make transactions widely.